Effects of Dietary Supplementation With Clostridium butyricum on the Amelioration of Growth Performance, Rumen Fermentation, and Rumen Microbiota of Holstein Heifers - Li, Yang; Wang, Yiqiang; Lv, Jingyi; Dou, Xiujing; Zhang, Yonggen (Frontiers in Nutrition, 2021)
In China, the use of antibiotics growth promoters as feed additives has been banned. The goal of raising dairy heifers is to gain a relatively high body weight on a high-fiber diet at first mating or calving, thus increasing economic benefits. The objective of this experiment was to explore the effects of supplemental Clostridium butyricum (C. butyricum) on growth performance, rumen fermentation and microbiota, and blood parameters in Holstein heifers. Twenty Holstein heifers (mean ± standard deviation (SD); age = 182 ± 4.20 d, body weight = 197.53 ± 5.94 kg, dry matter intake (DMI) = 6.10 ± 0.38 kg) were randomly assigned to one of two diets group for a 42-day feeding period: (1) basal diet (an untreated control group, i.e., the CON group) or (2) basal diet plus daily 2 × 108 (colony-forming unit, CFU) of C. butyricum per kg of DMI per heifer (the CB group). The results demonstrated that C. butyricum supplementation increased the average daily gain from d 21 to 42 and DMI compared to the control group. Supplementation with C. butyricum significantly decreased the molar proportion of acetate and the acetate to propionate ratio but increased the molar proportion of butyrate and propionate. Compared with the control group, the relative abundance of Butyrivibrio fibrisolvens, Ruminococcus albus, Ruminobacter amylophilus, Ruminococcus flavefaciens and Streptococcus bovis increased during the trial period in the CB group. However, C. butyricum had no significant effect on the blood parameters in Holstein heifers. In conclusion, these results show that feeding C. butyricum can improve growth performance and rumen fermentation without any negative impact on blood parameters in Holstein heifers.